Metallic or Metallic Oxide (Photo)catalysts for Environmental Applications - Hermans, Sophie; Mahy, Julien (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint is the compilation of the articles submitted in the Special Issue entitled "Metallic or Metallic Oxide (Photo)catalysts for Environmental Applications" from the journal Catalysts, which gives an overview of the latest advances in the development of metallic or metallic oxide (photo)catalytic materials, with environmental applications for the elimination of organic pollutants or the valorization of biomass.